Histopathologic Findings in 5 Patients With Hypomyopathic Dermatomyositis: The Importance of MHC-1 Expression on Myofibers. Issue 2 (December 2015) - El-Dokla, Ahmed M.; Aggarwal, Rohit; Oddis, Chester V.; Ali, Sara T.; Lacomis, David
Abstract : Abstract: Muscle histopathologic findings in hypomyopathic dermatomyositis (HDM) have not been adequately characterized. We sought to determine the results of conventional and immunohistopathology in HDM. Light microscopic and immunohistochemical analysis was performed on muscle from 5 patients with HDM without muscle weakness. Ages ranged from 49 to 56 years. Creatine kinase level was normal. Electromyography showed mild "myopathic" changes in 2. The median duration of skin disease before biopsy was 18 months. Abnormal major histocompatibility (MHC) class I immunoreactivity was noted in myofibers in all specimens even when conventional histopathology was normal (1 patient) or only mildly abnormal (3 patients). One specimen had the characteristic findings of dermatomyositis. Patchy MHC-1 expression on myofibers was a consistent finding in HDM in the absence of other histopathologic abnormalities. The presence of MHC-1 expression could indicate a degree of endoplasmic reticulum stress even in the absence of clinical muscle weakness, muscle enzyme abnormalities, or significant inflammatory infiltrate.